2007
DOI: 10.1111/j.1399-3038.2007.00543.x
|View full text |Cite
|
Sign up to set email alerts
|

Is breast feeding a risk factor for eczema during the first year of life?

Abstract: Breast feeding (BF) provides many advantages to the offspring; however, at present there is an ongoing debate as to whether or not it prevents allergic diseases. The aim of the current study was to investigate the effect of duration of BF on eczema in the first year of life. A birth cohort of 1128 infants was followed prospectively from 5 months of pregnancy. Data were collected using questionnaires, a medical examination and blood tests for allergy at the age of 1 yr. Breast feeding was not statistically sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 30 publications
2
37
0
1
Order By: Relevance
“…eggesbø and colleagues 8 assessed the association of the mother's use of antibiotics during pregnancy and the child's use of antibiotics during the first 6 months of life with the development of egg allergy in the child by the age of 3 years and found no association. increased risks of asthma, 16,18,20 eczema, [15][16][17] or hay fever 16 in offspring exposed to maternal use of antibiotics during pregnancy have been observed in some studies, although a null association with asthma has also been reported. 19 large cohort studies assessing child's own use of antibiotics have also reported both increased risk 9,13 and no risk 9,11,12 of various allergic diseases in childhood.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…eggesbø and colleagues 8 assessed the association of the mother's use of antibiotics during pregnancy and the child's use of antibiotics during the first 6 months of life with the development of egg allergy in the child by the age of 3 years and found no association. increased risks of asthma, 16,18,20 eczema, [15][16][17] or hay fever 16 in offspring exposed to maternal use of antibiotics during pregnancy have been observed in some studies, although a null association with asthma has also been reported. 19 large cohort studies assessing child's own use of antibiotics have also reported both increased risk 9,13 and no risk 9,11,12 of various allergic diseases in childhood.…”
Section: Discussionmentioning
confidence: 97%
“…[9][10][11][12][13][14] Maternal use of antibiotics has received much less attention. [15][16][17][18][19][20] Because antibiotics are commonly and often inappropriately used for upper respiratory tract infections, 21 the putative association between exposure to antibiotics and the risk of food allergies could have great public health impact. We explore whether a mother's and child's use of antibiotics is associated with cow's milk allergy in infancy in a population-based nested case-control study.…”
mentioning
confidence: 99%
“…15 studies were excluded for the following reasons: antibiotic exposure was collected retrospectively (n54) [9][10][11][12]; no report on wheeze and/or asthma, but other allergic outcomes only (n56) [13][14][15][16][17][18]; no association measure for wheeze or asthma separately but an overall outcome called ''atopy'' which also included eczema and/or hay fever (n51) [19]; only prenatal antibiotic use reported (n53) [20][21][22]; and adult population (n51) [23].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Therefore, this study will only be discussed in the following section, together with the remaining eight studies in which the positive association could not be explained by RC. [29] FOLIAKI [24] Ecological design SARIACHVILI [17] JOHNSON [16] VOOR [18] BREMNER [13] BREMNER [14] EGGESBO [15] FAROOQI [19] MITCHELL [10] THOMSEN [11] AWASTHI [9] WJST [12] JEDRYCHOWSKI [21] McKEEVER [22] BENN [20] CULLINAN [23] FIGURE 1. Results of the literature search and selection of studies.…”
Section: Reverse Causationmentioning
confidence: 99%
“…Existem também diferenças na presença de atopia por sexo da criança e conforme seu pai ou sua mãe tenham sido portadores de asma 35 . Outro estudo prospectivo de mais de mil crianças belgas seguidas desde a gravidez até os primeiros 12 meses, também mostrou que no primeiro ano de vida a amamentação não tem efeito protetor quanto a eczema 36 . Mesmo revisões sistemáti-cas não conseguem dar uma resposta sobre essa relação "amamentação/atopia", o que indica que melhores estudos precisam ser elaborados.…”
Section: Introductionunclassified